1980
DOI: 10.1254/jjp.30.807
|View full text |Cite
|
Sign up to set email alerts
|

Possible embryogenetical differences of the dog venous system in sensitivity to vasoactive substances.

Abstract: Abstract-Using isolated dog veins, we examined whether correlations exist between the regional differences in sensitivity to drugs and their embryogenesis.Twelve different veins were dissected. In the analysis, the data obtained previously for the inferior vena cava were also included. Spiral strips were prepared and the contractile responses to cumulative application of norepinephrine (NE), 5-hydroxytryptamine (5-HT), histamine (Hist) and acetylcholine (ACh) were recorded isometrically.For each drug, a histog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…The preconstrictions evoked by me thoxamine slighly varied among the veins, but the regional difference in endothelium-depen dent relaxations were not related to the varia tion of the preconstriction levels (see, for in stance, the results of jugular vein and azygos veins in Table 1). Acetylcholine is known to cause the contractile responses in the veins showing the endothelium-dependent relaxa tions in the present study (6,9). However, the influence of such contractions on the observed relaxation responses seemed unlikely, because ACh-induced contractile responses of these veins occurred at higher concentration than 10-6 M (6, 9), whereas the endothelium dependent relaxations evoked by ACh were seen at lower concentrations than this, and maximum responses were obtained around 3x10-7 M. Thus, the present study indicated that the endothelium-dependent relaxation responses to ACh are regionally different in the canine venous system.…”
mentioning
confidence: 60%
See 3 more Smart Citations
“…The preconstrictions evoked by me thoxamine slighly varied among the veins, but the regional difference in endothelium-depen dent relaxations were not related to the varia tion of the preconstriction levels (see, for in stance, the results of jugular vein and azygos veins in Table 1). Acetylcholine is known to cause the contractile responses in the veins showing the endothelium-dependent relaxa tions in the present study (6,9). However, the influence of such contractions on the observed relaxation responses seemed unlikely, because ACh-induced contractile responses of these veins occurred at higher concentration than 10-6 M (6, 9), whereas the endothelium dependent relaxations evoked by ACh were seen at lower concentrations than this, and maximum responses were obtained around 3x10-7 M. Thus, the present study indicated that the endothelium-dependent relaxation responses to ACh are regionally different in the canine venous system.…”
mentioning
confidence: 60%
“…However, there are only a few reports de scribing the endothelium-dependent re sponses of veins (3,4). In previous papers, we repeatedly indicated that the canine venous system consists of veins characteristically different in pharmacological responses (5)(6)(7)(8)(9). Therefore, in the present study, distribution of endothelium-dependent relaxation re sponses in the venous system was inves tigated by using 15 canine veins selected systematically (5,6).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…In the dog, the splenic vein has a high sensitivity to noradrenaline and 5-hydroxytryptamine, like the veins of the body wall or extremities, and is not so sensitive to histamine unlike the main portal or mesenteric veins (Ishikawa et al, 1980). The gastric vein is said to be derived embryologically from the foregut plexus, while another portal segment derived from the vitelloumbilical veins (Butler, 1952) and the splenic vein is a shunt vein between the spleen and the portal system (Miki, 1983).…”
Section: Discussionmentioning
confidence: 99%